High-Speed Rail Opening and Green Innovation—Evidence From China - Yu, Xiaolin; Wan, Kai (Frontiers in Environmental Science, 2022)
Significant progress has been achieved in the construction of transportation infrastructure in China, where a high-speed rail network of considerable scale and high operational speed has been formed. Against the backdrop of China’s current keynote on “carbon peaking” and “carbon neutrality,” the high-speed rail as a modern, green mode of transport, has become a key force in promoting green technological innovation and maintaining sustainable economic development. This paper focuses on the relationship between the opening of high-speed rail and urban green innovation and the mechanisms behind it. This study utilized panel data on Chinese cities from 2000 to 2018, taking the opening of high-speed rail as a quasi-natural experiment. It focuses on the impact and mechanism of the opening of the high-speed railway on urban green innovation by using the double-difference space Durbin model. Findings indicate that high-speed rail plays a significant role in promoting urban green innovation and that the spatial spillover effect is substantial. The results of the heterogeneity test indicate that high-speed rail can enhance urban green innovation in non-resource-based cities. The impact mechanism of high-speed railways on urban green innovation mainly comes from the flow of innovative personnel and capital, a strategy of local governments to strengthen environmental regulations and improve regional advantages. This paper also indicates that high-speed rail has an inverted U-shaped trend in promoting urban green innovation, and the optimal radius is 200 km from the nucleus city.